Does Zakat Fitrah Distribution Truly Satisfy the Community? Evidence from Aceh Tamiang - Fahrizal, Muhammad; Habibi, Khairul; Fakhruddin, Fakhruddin (International Journal of Islamic Thought and Humanities, 2026)
This study aims to analyze the effect of the distribution of zakat fitrah on community satisfaction in Gampong Kebun Tanah Terban, Karang Baru District, Aceh Tamiang Regency. The study uses a quantitative, survey-based approach. Data were collected from 100 respondents who were zakat recipients through observation, questionnaires, and documentation. Sampling was carried out using simple random sampling. The collected data were analyzed using simple linear regression in SPSS version 25. The results indicate that zakat fitrah distribution has a positive and significant effect on community satisfaction, with a regression coefficient value of 0.777 and a significance level of 0.000 (<0.05). The coefficient of determination (R²) of 0.508 indicates that 50.8% of community satisfaction is explained by the zakat fitrah distribution, while the remaining 49.2% is explained by other factors. These findings suggest that the more effective, fair, and transparent the zakat fitrah distribution, the higher the community’s satisfaction level. The study contributes to strengthening the management of zakat as an instrument of Islamic social justice and community welfare.